Sparking Signals Kinases as Molecular Signaltransducers and Pharmacological Drug Targets in Inflammation - Baier, Gottfried; Schraven, Burkhart; Zügel, Ulrich; Bonin, Arne.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Protein phosphorylation is an essential post-translational modification that modulates cell–cell communication. Substrate phosphorylation by protein kinases controls intracellular signal transduction pathways that mediate cell proliferation, migration, differentiation, and metabolism. The importance of the protein kinase family is underscored by numerous disease states that arise due to dysregulation of kinase activity. Recent progress in understanding the molecular regulation of kinases has led to the development of new therapeutics based on the inhibition of kinase activity. Inhibitors that target protein kinases have proven efficacious in clinical settings and their continued development is the current focus of many drug discovery groups.
Proteomics-Based Strategies in Kinase Drug Discovery -- PKC Isotype Functions in T Lymphocytes -- Migration, Cell–Cell Interaction and Adhesion in the Immune System -- Molecular Mechanisms that Control Leukocyte Extravasation Through Endothelial Cell Contacts -- Fragment-Based Drug Discovery Using Rational Design -- Systems Biology of T Cell Activation -- Solving the IRAK-4 Enigma: Application of Kinase-Dead Knock-In Mice -- Sensing, Presenting, and Regulating PAMPS -- The Role of Diacylglycerol Kinases in T Cell Anergy.
Keywords: Pharmacology; Immunology; Biochemistry; Pharmacology/Toxicology.; Immunology; Biochemistry, general